MUNK TENGERY AND HOLOGRAPHIC UNIVERSE - O.Lhagva (Acta Mongolica, 2011)
In this essay, in the light of the Holographic paradigm, the ancient Mongolian nomadic worldviewMunk Tengery is considered. Prominent physicist D. Bohm suggests a paradigm of holographic universe,con the basis of the most fundamental experiments of XX century. According to the holographic paradigm, seemingly solid-looking materials and separateness of things surrounding us are fully illusory, and all realities in the universe are infinitely interconnected and implicated.